2016
DOI: 10.1007/s12011-016-0663-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arctium lappa on Cadmium-Induced Damage to the Testis and Epididymis of Adult Wistar Rats

Abstract: The protective role of Arctium lappa (AL) on the testes of rats acutely exposed to cadmium (Cd) was tested. The rats were randomly divided into a control group (C-group) and three major experimental groups, which were further subdivided into minor groups (n = 6) according to the experimental period (7 or 56 days). The C-group was subdivided into C-7 and C-56 [receiving a single saline solution, intraperitoneal (i.p.), on the first day]; the AL-group, AL-7, and AL-56, received AL extract (300 mg/kg/daily); the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…(2007) [35] observed that animals exposed to higher concentrations of Ni in a shorter time of exposure showed a reduction in DT and EH, in addition to an increase in the lumen diameter (LD). However, similar results to the present study were observed by Lima et al (2018) [25] in rats after exposure of As 5+ and As 3+ (0.01 and 10 mg/L for 56 days), by Oliveira (2010) [59] with Ni (0.67 and 1.34 g/L for 60 days) and by Li et al (2016) [37] and Predes et al (2016) [38] with Cd (0.2 mg/L for 24 hours and 1.2 mg/kg for 7 and 56 days, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…(2007) [35] observed that animals exposed to higher concentrations of Ni in a shorter time of exposure showed a reduction in DT and EH, in addition to an increase in the lumen diameter (LD). However, similar results to the present study were observed by Lima et al (2018) [25] in rats after exposure of As 5+ and As 3+ (0.01 and 10 mg/L for 56 days), by Oliveira (2010) [59] with Ni (0.67 and 1.34 g/L for 60 days) and by Li et al (2016) [37] and Predes et al (2016) [38] with Cd (0.2 mg/L for 24 hours and 1.2 mg/kg for 7 and 56 days, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…However, unlike the present study, the authors reported higher germinative epithelium loss, especially in animals that received 1.8 and 2.2 mg/kg of CdCl 2 , to increased testicular concentration of Ca and consequent dystrophic calcification. Predes et al [4, 58] also observed disorganized seminiferous tubules, besides reduced testicular weight of Wistar rats receiving a single dose of 1.2 mg/kg CdCl 2 i.p. and evaluated after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Arctium lappa L. (popularly known as burdock) is widely used in popular medicine worldwide as a diuretic and antipyretic agent and has also been used to treat hypertension, gout, hepatitis, and other inflammatory disorders [17,18]. Interest in A. lappa extracts has grown due to their ample therapeutic potential [19,20,21].…”
Section: Introductionmentioning
confidence: 99%